2015
DOI: 10.1371/journal.pone.0139009
|View full text |Cite
|
Sign up to set email alerts
|

“If You Are Not Circumcised, I Cannot Say Yes”: The Role of Women in Promoting the Uptake of Voluntary Medical Male Circumcision in Tanzania

Abstract: Voluntary Medical Male Circumcision (VMMC) for HIV prevention in Tanzania was introduced by the Ministry of Health and Social Welfare in 2010 as part of the national HIV prevention strategy. A qualitative study was conducted prior to a cluster randomized trial which tested effective strategies to increase VMMC up take among men aged ≥20 years. During the formative qualitative study, we conducted in-depth interviews with circumcised males (n = 14), uncircumcised males (n = 16), and participatory group discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…Such influence through beliefs about sexual performance has also been reported in many studies in WHO priority SMC countries [30, 28, 21, 36, 29, 3739] and elsewhere [40]. Perception of partner preference for circumcised men has also been reported in other places [34, 24, 41, 26, 40, 42].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Such influence through beliefs about sexual performance has also been reported in many studies in WHO priority SMC countries [30, 28, 21, 36, 29, 3739] and elsewhere [40]. Perception of partner preference for circumcised men has also been reported in other places [34, 24, 41, 26, 40, 42].…”
Section: Discussionsupporting
confidence: 53%
“…A study in Zambia found that women’s acceptance of circumcision and discussion with partners influenced men’s readiness to undergo SMC [25, 22] and in Kenya, a study documented that some women who were ‘more knowledgeable’ about circumcision educated their partners and encouraged them to go for the service [34]. Studies in Botswana and Tanzania showed both direct and indirect influence as well, with women using “soft” language to convince partners, mindful not to endanger their marriages or relationships, while others even denied partners sex to effect circumcision decisions [28, 29]. However, in contrast to this, in a study in Rakai, Uganda [35], conducted before the national scale up of SMC, female partners were reported as deterring rather than motivating the decision to get circumcised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth interviews and participatory group discussions were used to identify barriers and facilitators to uptake of VMMC among men aged 20–34 years, whereas DCEs assessed the intervention components that could potentially increase VMMC uptake among 20–34 year olds. These findings informed specific components of the intervention [22,23]. The intervention applied information, motivation, and behaviour theory to findings from the formative study [24].…”
Section: Methodsmentioning
confidence: 78%
“…Our formative work also highlighted the need for an expanded role for women in VMMC communication strategies [23]. This study used mobile information booths to provide counselling and education services to female partners of VMMC clients.…”
Section: Discussionmentioning
confidence: 99%